2010
DOI: 10.1371/journal.pbio.1000355
|View full text |Cite
|
Sign up to set email alerts
|

Spadin, a Sortilin-Derived Peptide, Targeting Rodent TREK-1 Channels: A New Concept in the Antidepressant Drug Design

Abstract: We found that spadin, a natural peptide derived from sortilin, blocks the mouse TREK-1 channel and might be an efficient and fast-acting antidepressant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
200
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(232 citation statements)
references
References 51 publications
(100 reference statements)
12
200
1
2
Order By: Relevance
“…In contrast, TREK-1 and TREK-2 chan-nels are regulated differently by extracellular (EC) 2 acidification; TREK-1 is inhibited, and TREK-2 is activated (16,17). TREK-1 is inhibited by the sortilin-derived neuropeptide spadin, and TREK-2 is insensitive to spadin (18,19). Recently, we described the differential pharmacological effect of the polycationic dye ruthenium red (RR) on TREK channels; TREK-2 is potently inhibited by the dye, whereas TREK-1 is insensitive to RR (20).…”
mentioning
confidence: 99%
“…In contrast, TREK-1 and TREK-2 chan-nels are regulated differently by extracellular (EC) 2 acidification; TREK-1 is inhibited, and TREK-2 is activated (16,17). TREK-1 is inhibited by the sortilin-derived neuropeptide spadin, and TREK-2 is insensitive to spadin (18,19). Recently, we described the differential pharmacological effect of the polycationic dye ruthenium red (RR) on TREK channels; TREK-2 is potently inhibited by the dye, whereas TREK-1 is insensitive to RR (20).…”
mentioning
confidence: 99%
“…TREK1 knockout mice (TREK1 −/− ) display a depression-resistant phenotype (18). Recently, it was reported that spadin, a sortilin-derived peptide, targets TREK1 to generate an antidepressive effect (35). In addition, fluoxetine, the chemical name of the widely used antidepressant Prozac, has been shown to inhibit TREK1 at clinical concentrations (15).…”
Section: Discussionmentioning
confidence: 99%
“…TREK1 has been implicated in depression (18,34,35) and has been proposed to be a therapeutic target of the antidepressant fluoxetine, which has been shown to inhibit channel activity (15). The E306A mutation was found to have reduced fluoxetine inhibition (15), suggesting a possible involvement of the TREK1 C terminus.…”
Section: Fluoxetine Inhibition Of Trek1 Channel Activity By Membranementioning
confidence: 99%
“…L'autre consiste à modifier des protéines natives avec des molé-cules chimiques synthétiques sensibles cible dans le traitement de la dépres-sion [7]. En accord avec cette hypothèse, la spadine, un peptide dérivé de la sortiline qui inhibe TREK1, a un effet antidépresseur [8]. Chez l'homme, une étude a également rapporté un rôle de TREK1 dans la régulation de l'humeur et dans la résistance au traitement antidépresseur.…”
Section: Les Canaux Potassique à Deux Domaines Poresunclassified